Abnormal Size-Dependent Modulation of Motion Perception in Children with Autism Spectrum Disorder (ASD) - Sysoeva, Olga V.; Galuta, Ilia A.; Davletshina, Maria S.; Orekhova, Elena V.; Stroganova, Tatiana A. (Frontiers in Neuroscience, 2017)
Excitation/Inhibition (E/I) imbalance in neural networks is now considered among the core neural underpinnings of autism psychopathology. In motion perception at least two phenomena critically depend on E/I balance in visual cortex: spatial suppression (SS), and spatial facilitation (SF) corresponding to impoverished or improved motion perception with increasing stimuli size. While SS is dominant at high contrast, SF is evident for low contrast stimuli, due to the prevalence of inhibitory contextual modulations in the former, and excitatory ones in the latter case. Only one previous study (Foss-Feig et al., 2013) investigated SS and SF in Autism Spectrum Disorder (ASD). Our study aimed to replicate previous findings, and to explore the putative contribution of deficient inhibitory influences into an enhanced SF index in ASD – a cornerstone for interpretation proposed by previous study. The SS and SF were examined in 40 boys with ASD, broad spectrum of intellectual abilities (63 < IQ < 127) and 44 typically developing (TD) boys, aged 6-15 years. The stimuli of small (1°) and large (12°) radius were presented under high (100%) and low (1%) contrast conditions. Social Responsiveness Scale and Sensory Profile Questionnaire were used to assess the autism severity and sensory processing abnormalities. In our ASD group the SS index was atypically reduced, while the SF index was abnormally enhanced. The presence of abnormally enhanced SF in children with ASD was the only consistent finding between our study and that of Foss-Feig at el. While the SS and SF indexes were strongly interrelated in TD participants, this correlation was absent in their peers with ASD. In addition, the SF index but not the SS index correlated with the severity of autism and the poor registration abilities. The pattern of results is partially consistent with the idea of hypofunctional inhibitory transmission in visual areas in ASD. Nonetheless, the absence of correlation between SF and SS indexes paired with a strong direct link between abnormally enhanced SF and autism symptoms in our ASD sample emphasizes the role of the enhanced excitatory influences by themselves in the observed abnormalities in low-level visual phenomena found in ASD.